2016
DOI: 10.18388/abp.2016_1272
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin ameliorates spinal cord injury via antioxidant and anti-inflammatory effects

Abstract: Spinal cord injury (SCI) is one of the most severe traumatic injuries that results in dysfunction of limbs and trunk below the damaged section. Recent studies have shown that gastrodin (GAS) could improve the recovery of SCI. In the current study, we aimed to examine the possible mechanism underlying the effect of GAS on recovery of SCI in rats. In rats with SCI, GAS improved locomotor functions and decreased permeability of blood-spinal cord barrier, as illustrated by increase of Basso-Beattie-Bresnahan score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The late response of the endothelial cells was characterized by the production of various antioxidant proteins (Figure 7). It is known that antioxidants proteins have beneficial effects on the BBB damage responses and play a major role in its recovery from damage (Du et al 2016;Janyou et al 2017;Jumnongprakhon et al 2015;Lim et al 2016;Mendes Arent et al 2014;Benvenisti-Zarom and Regan 2007). Antioxidant proteins like nuclear factor-like 2 protein (Nrf2) and heme oxygenase-1 (HMOX-1) have been defined as oxidative-sensor proteins.…”
Section: Effect Of Agnps On the Blood Brain Barrier Endothelial Cell mentioning
confidence: 99%
See 1 more Smart Citation
“…The late response of the endothelial cells was characterized by the production of various antioxidant proteins (Figure 7). It is known that antioxidants proteins have beneficial effects on the BBB damage responses and play a major role in its recovery from damage (Du et al 2016;Janyou et al 2017;Jumnongprakhon et al 2015;Lim et al 2016;Mendes Arent et al 2014;Benvenisti-Zarom and Regan 2007). Antioxidant proteins like nuclear factor-like 2 protein (Nrf2) and heme oxygenase-1 (HMOX-1) have been defined as oxidative-sensor proteins.…”
Section: Effect Of Agnps On the Blood Brain Barrier Endothelial Cell mentioning
confidence: 99%
“…The antioxidant proteins were significantly upregulated after 48 h AgNPs exposure compared to its expression at 24 h exposure. The anti-oxidant proteins NQO1 and GCLM are also reported to be involved in endogenous cellular stress responses and to protect cells from ROS-induced damage and cell death (Du et al 2016;Lin et al 2017;Zhang, Davies, and Forman 2015). Thus, increased production of these proteins after AgNPs exposure may indicate the activation of various oxidative and inflammatory injury response cascades in response to AgNPs., NQO1 expression was elevated after 48 h AgNPs exposure.…”
Section: Effect Of Agnps On the Blood Brain Barrier Endothelial Cell mentioning
confidence: 99%
“…Elevated levels of Bcl-2 and a decrease in Bax indicate that cells are more resistant to apoptosis and should be a marker of protective drug action, and vice versa. Studies have found that oxidative stress caused by high doses of NaF leads to mitochondrial damage, leading to osteogenic and osteoclast apoptosis [32,36]. The caspase cascade is triggered by caspase-9, after which caspase-3 becomes activated by caspase-9.…”
Section: Group T Normal Mild Moderate Severementioning
confidence: 99%
“…In ancient China, G. elata was widely used to treat headache, dizziness, paralysis, epilepsy, joint pain, and numbness of limbs ( Zhan et al., 2016 ). Some studies on its pharmacological properties have shown that G. elata has neuroprotective and antioxidant functions and could be used as an anti-inflammatory and antipsychotic drug ( Kumar et al., 2013 ; Hu et al., 2014 ; Du et al., 2016 ; Wang et al., 2016 ). The pharmacological mechanisms of potential anticonvulsant activity of arrow G. elata have been extensively studied, which is similar to the mechanisms of known antiepileptic drugs ( Wu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%